Restorative Approach in Family Conflict Resolution Through ADR Process - Fany Kambu; Rakia, A. Sakti R.S.; Yati, Sri; Muh Akdharisa SJ (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze the effectiveness of restorative approaches in resolving family conflicts through Alternative Dispute Resolution (ADR) mechanisms and to identify factors that support and hinder their implementation at the community level. The methods used in this research are empirical legal methods that combine primary data obtained through interviews with relevant parties such as mediators, community leaders, and families involved in disputes as well as secondary and tertiary data obtained through literature studies. All data are analyzed qualitatively using a deductive approach. The novelty of this research lies in the integration of justice-based restorative principles with Indonesian socio-cultural values, particularly the concept of deliberation to reach consensus as the basis for resolving family conflicts outside of court. The findings show that the restorative approach in ADR is able to provide a more humanistic alternative to resolution because it emphasizes relationship restoration, equal dialogue, and social balance. Processes such as mediation, negotiation, and conciliation have been proven to be in line with local cultural values and effective in reducing conflict escalation and the potential for violence within families. However, implementation in the field still faces a number of obstacles, including low public literacy regarding ADR, the influence of patriarchal culture that weakens the position of women, the limited number of professional mediators, and the complexity of emotional aspects and child protection. The conclusion is that the restorative approach through ADR has significant potential as a sustainable solution in resolving family conflicts. Its effectiveness depends on strengthening the capacity of community-based mediators, increasing public legal awareness, and drafting regulations that are more responsive to the needs of non-litigious family dispute resolution.